IMPLEMENTASI MODEL COLLABORATIVE LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM GUNA MENINGKATKAN HASIL BELAJAR SISWA - Agus Sulthoni Imami; Dirham Sukma Sahrur Romadhon; M. Mahbubi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the effect of implementing a collaborative learning model in Islamic Religious Education (PAI) learning on improving learning outcomes and strengthening students' social skills in junior high schools. This study was motivated by the phenomenon of declining student learning outcomes and lack of student involvement in PAI learning, even though the material taught was very relevant in character building. The approach used in this study was a qualitative approach with a case study research type. Data collection techniques used included interviews, observations, and documentation. The data obtained were analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of a collaborative learning model can improve student learning outcomes, especially in understanding PAI material, as well as strengthening their social skills, such as cooperation, communication, and respect for differences of opinion. The contribution of this study is to provide new insights into the importance of a collaboration-based learning approach in the context of Islamic Religious Education at the junior high school level, as well as providing recommendations for optimizing this learning model in improving the quality of more holistic education